2013
DOI: 10.1007/s00784-013-1039-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bone insertion level of the implant on the fracture strength of different connection designs: an in vitro study

Abstract: When implants are used in areas where there is a possibility of bone loss, the selection of a connection type is an important consideration for the longevity of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
(17 reference statements)
2
32
0
1
Order By: Relevance
“…The implant diameter relative to the dimension of the supporting bone is critical for successful treatment. 21 The average maximum bite force for adults in the premolar and molar regions is 789 N for men and 596 N for women. 22 In our study, fracture strength after static loading of the specimens was significantly higher for all groups when the CHR was 8 mm.…”
Section: Figurementioning
confidence: 99%
“…The implant diameter relative to the dimension of the supporting bone is critical for successful treatment. 21 The average maximum bite force for adults in the premolar and molar regions is 789 N for men and 596 N for women. 22 In our study, fracture strength after static loading of the specimens was significantly higher for all groups when the CHR was 8 mm.…”
Section: Figurementioning
confidence: 99%
“…Those factors directly affect the surrounding bone tissue, causing resorption and even leading to the loss of the implant. Some studies show that the internal connections have a smaller space between the implant and the abutment and thus lower risk of biological and mechanical problems 7,[16][17][18] . As in this study, in order to determine which implant system causes less damage to the perimplant tissues, some studies compared the different types of prosthetic connections 7,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The internal connections, especially the Morse cone, have shown better performance over the external connections in some experimental studies 1,3,10,[17][18] . Goiato et al 3 , showed better distribution of loads on implants with Morse cone connections when compared to external hexagon connections.…”
Section: Perimplant Marginal Bone Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pode-se justificar a discrepância de resultados nos modelos com recobrimento da plataforma do implante (AB-C), verificados no estudo fotoelástico prévio de Gehrke et al (2014) Uma inserção mais profunda proporciona uma resistência superior às forças externas, particularmente àquelas envolvidas com a reposição de implantes na região de molar (Gehrke et al, 2014). Apesar disso excelentes resultados em estudos de larga escala foram obtidos inserindo os implantes ao nível da crista (Mangano et al, 2009(Mangano et al, , 2011.…”
Section: Ordemanddeandfranjaand Cargaandexcêntricaunclassified